The Application Pattern of Care Management Principles at Darul Arafah Raya Islamic Boarding School, Deli Serdang Regency - Ade Putra; Mesiono; Syaukani (Didaktika: Jurnal Kependidikan, 2024)
This research investigates the application and effectiveness of parenting management principles at Darularafah Raya Islamic Boarding School in Deli Serdang Regency, North Sumatra. Pesantrens, as traditional Islamic educational institutions, are crucial in shaping students' morals and behaviors alongside their academic development. This study highlights the importance of effective management to align pesantren operations with contemporary educational needs while maintaining traditional values. The research employs a qualitative approach, including observations, interviews, and document analysis, to understand the caregiving management patterns at the boarding school. The principles guiding the caregivers include sincerity, simplicity, independence, and devotion, along with truthfulness (Ash-shidqu), trustworthiness (al-Amanah), communication (at-Tabligh), wisdom (al-Fathanah), and steadfastness (al-Istiqamah). These principles are consistently implemented in the daily activities and interactions with students. Findings reveal that the pesantren adopts a democratic approach to parenting management, allowing freedom of expression within the framework of the institution's vision and mission. This approach fosters a supportive and structured environment, enhancing students' confidence, discipline, and moral development. Caregivers play a crucial role in setting boundaries, enforcing rules, and guiding students' behavior and decision-making, ensuring a balanced and respectful educational atmosphere. The study concludes that the democratic application of parenting management principles at Darularafah Raya Islamic Boarding School effectively supports the holistic development of students, preparing them for personal and global challenges. The consistent implementation of these principles by caregivers contributes significantly to the institution's success and the students' overall growth.